High integrity mental health services for children: focusing on the person, not the problem. (3rd April 2017) - Wolpert, M; Vostanis, P; Martin, K; Munk, S; Norman, R; Fonagy, P; Feltham, A
Abstract : M Wolpert and colleagues discuss how the principles of high integrity healthcare can improve mental health services for children and young people